Nordic Seas high resolution model system - a first test run - Winther, Nina Gjerde (Zenodo, 2007)
This work is part of the project ”Ocean weather and ecosystem in the Nordic seas" with the principle objectives and sub-goals: To further build on our competence in ”operational oceanography” focusing on basic research: – For improving and validating our TOPAZ system nested for the Nordic Seas and key Norwegian coastal regions. – To implement and validate a new formulation for the ecosystem of the Nordic Seas. – To incorporate measurements of the internal ocean and biochemical variability. – To design and assess a cost effective configuration of a Nordic Seas network of observations. – To demonstrate the improved TOPAZ modelling and data assimilation system in operation over a period of one year and compare the output with other existing operational products. The work presented in this report is a first trial to set up a realistic model system for the Nordic Seas. The physical ocean model used is HYCOM. This report presents the model set up and results from a two month test simulation. NERSC Technical Report no. 285. Funded by the Research Council of Norway.